Critical Analysis of the Implementation of Sustainable Agricultural Land Protection - Dahiri, Dahiri (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2021)
The conversion of agricultural paddy fields to non-paddy fields is estimated at 100,000 hectares per year. If the conversion of productive land functions is not resolved, it is estimated that in the next 40-50 years, the rice field area will be used up as non-agricultural areas. The purpose of this study is to analyze the factors that can affect sustainable food agriculture land and the efforts that need to be made by the government to protect sustainable food agricultural land. The research method used to descriptive statistics and normative juridical approach. The results show that there is no incentive for local governments to include PLP2B in their RTRW, incentives for farmers who are committed to PLP2B, and financing in extensification development activities not based on the IKK. Therefore, the government’s efforts to protect sustainable food agricultural land are providing incentives for local governments to determine the area of sustainable food agriculture in the RTRW with incentives in the form of DAK in agriculture, providing incentives for farmers who participate in PLP2B by providing pre-harvest and postharvest agricultural machine tools, and calculation of extensification costs using the IKK.